2013
DOI: 10.1111/epi.12391
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive brivaracetam for uncontrolled focal and generalized epilepsies: Results of a phase III, double‐blind, randomized, placebo‐controlled, flexible‐dose trial

Abstract: SUMMARYPurpose: To evaluate the safety and tolerability of adjunctive brivaracetam (BRV), a high-affinity synaptic vesicle protein 2A (SV2A) ligand, in adults with uncontrolled epilepsy. Efficacy was also assessed in patients with focal seizures as a secondary objective, and explored by descriptive analysis in patients with generalized seizures. Methods: This was a phase III, randomized, double-blind, placebo (PBO)-controlled flexible dose trial (N01254/NCT00504881) in adults (16-70 years) with uncontrolled ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
205
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(242 citation statements)
references
References 16 publications
(25 reference statements)
22
205
1
5
Order By: Relevance
“…Although there was only a limited group receiving concomitant levetiracetam (<20%), this finding has been reported in other studies (2,3,10,11). These results suggest that using levetiracetam in combination with brivaracetam decreases the effect of brivaracetam.…”
Section: Brivaracetam a Novel Antiepileptic Drug: Is It Effective Ansupporting
confidence: 70%
“…Although there was only a limited group receiving concomitant levetiracetam (<20%), this finding has been reported in other studies (2,3,10,11). These results suggest that using levetiracetam in combination with brivaracetam decreases the effect of brivaracetam.…”
Section: Brivaracetam a Novel Antiepileptic Drug: Is It Effective Ansupporting
confidence: 70%
“…Incidence of TEAEs was highest during the dose-finding period, decreasing during the A c c e p t e d M a n u s c r i p t 31 maintenance period (brivaracetam: 56.0% to 36.8%, placebo: 55.4 to 40.9%) (Kwan et al, 2014).…”
Section: Tolerability and Adverse Effect Profilementioning
confidence: 93%
“…Two fixed-dose (N01253; NCT00464269 and N01252; NCT00490035) Ryvlin et al, 2014), and one flexible dose (N01254; NCT00504881) (Kwan et al, 2014), prospective, multicenter, randomized, double-blind, placebo-controlled, parallel-group Phase III trials have been completed.…”
Section: Phase III Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis involving two dose-ranging phase II studies showed that BRV might be efficacious and well tolerated as an adjunctive treatment in patients with refractory partial onset seizures (Gao et al, 2013). Recently, there have been increasing interests in the application of BRV in epilepsy patients and at least three phase III trials were published in year 2014 (Biton et al, 2014;Ryvlin et al, 2014;Kwan et al, 2014). Owing to recently published phase III clinical trials, the previous meta-analysis has become outdated.…”
Section: Introductionmentioning
confidence: 99%